Absolute poverty: When necessity displaces desire - Robert C. Allen (Luxembourg Income Study (LIS), 2017)
A new basis for an international poverty measurement is proposed based on linear programming for specifying the least cost diet and explicit budgeting for non-food spending. This approach is superior to the World Bank's '-a-day' line because it is (1) clearly related to survival and well being, (2) comparable across time and space since the same nutritional requirements are used everywhere while non-food spending is tailored to climate, (3) adjusts consumption patterns to local prices, (4) presents no index number problems since solutions are always in local prices, and (5) requires only readily available information. The new approach implies much more poverty than the World Bank's, especially in Asia.
Keywords: I12; I32; O61; O63; 330; absolute poverty; diet problem; linear programming; World Bank poverty line